Robust mixture linear EIV regression models by t-distribution - Liu, Yantong (Kansas State University, 2012)
A robust estimation procedure for mixture errors-in-variables linear regression models is proposed in the report by assuming the error terms follow a t-distribution. The estimation procedure is implemented by an EM algorithm based on the fact that the t-distribution is a scale mixture of normal distribution and a Gamma distribution. Finite sample performance of the proposed algorithm is evaluated by some extensive simulation studies. Comparison is also made with the MLE procedure under normality assumption.
Keywords: Robust estimation; Linear errors-in-variables model; EM algorithm; Mixture; T-distribution; Statistics (0463)